Cytotoxicity of Turmeric Extract (Curcuma longa linn.) on BHK21 Fibroblast Cells - Azzahra, Nadya Fithrie; Indrawati, Retno; Diyatri, Indeswati (GoAcademica Research & Publishing, 2024)
Wound healing is the process of recovery from injury to stop bleeding, and fibroblasts play a crucial role in the healing process and contribute to the regeneration of periodontal tissue. Turmeric extract (Curcuma longa linn.) is an alternative treatment that uses natural ingredients with antibacterial, antioxidant, and anti-inflammatory properties. The aim of this study is to demonstrate the toxicity of turmeric extract (Curcuma longa linn.) on BHK21 fibroblast cells. Turmeric extract (Curcuma longa linn.) was administered at concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.12%, 1.56%, and 0.78% to BHK-21 fibroblast cells, and its cytotoxicity was tested using the MTT Assay. The research results show that the percentage viability of fibroblast cells decreases successively with concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.12%, 1.56%, and 0.78%, with the highest percentage at a turmeric extract concentration of 0.78% and the lowest at a concentration of 100%. The conclusion of this study is that turmeric extract (Curcuma longa linn.) is not cytotoxic to BHK-21 fibroblast cells at concentrations of 0.78%, 1.56%, and 3.12%.